In Vitro Activity of Pandan (Pandanus amaryllifolius) Leaves Crude Extract Against Selected Bacterial Isolates - Dumaoal, Oliver Shane R.; Alaras, Ladylyn B.; Dahilan, Sarah, Karen G.; Depadua, Andrea A.; Pulmones, Christine Joy G. (JPAIR Multidisciplinary Research, 2010)
Nowadays, there is a demand for novel drugs to prevent these infections and the emergence from mutation of microorganisms. Given the rising incidence of resistance to synthetic antibiotics and in light of the rising costs of medicines it is well-timed to search for natural products such as plant derived antimicrobial drugs to reduce the resistance of microorganisms. Pandan (Pandanus amaryllifolius), in addition to synthetic alternatives, has the potential of antibacterial activity. The antibacterial properties of pandan crude extract however are not yet scientifically established. For that reason, the research proponents of this study aims to assess the antibacterial properties of pandan with the end view of providing low cost of medications and the prevention of resistance. This research analyzed the in vitro activity of pandan leaves crude extract against bacterial isolates such as Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922 and Pseudomonas aeruginosa ATCC 27853. About 1 kilogram of freshly collected pandan leaves was subjected to water distillation and the filtrate was concentrated using rotary evaporator. The crude extract was then used for the phytochemical analysis. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of pandan against the said microorganisms were examined. This study also determined the stability of pandan as to pH and temperature.